Computer modeling of the mechanisms of melting metal nanoparticles of different shapes - A. E. Bandin; M. S. Zhukovsky; S. A. Beznosyuk (Chimica Techno Acta)
The report presents the basic models describing the melting temperature of nanomaterials based on different concepts of the structure of matter. It takes under consideration some drawbacks described models. Methods of computer experiment show the effect of the matrix and forms of nanoparticle on its melting point. Some mechanisms of melting metal nanoparticles of different shapes are described. Thermodynamic models give a qualitative description of the melting temperature of nanomate-rials, not taking into account any impact form nanoparticles, nor matrix in which the nanoparticle is, thus showing that the sample temperature will decrease with decreasing the size of nanoparticles. Statistical models take into account these effects and show that the melting temperature of the nanoparticles can either increase or decrease with decreasing the size of nanoparticles.